2021
DOI: 10.24093/awej/vol12no2.16
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Metadiscursive Markers in Letters of Recommendation: An Investigation of Gender Variations

Abstract: This study aimed to investigate gender variations in letters of recommendation. It used the metadiscourse theory with respect to the following resources: hedges, boosters, attitude markers, engagement markers, and self-mentions. The findings showed that hedges devices were the least frequent in both groups, but at the same time were used more by males compared to female recommenders. Boosters, on the other hand, were highly frequent in both corpora and, like hedges, were employed more frequently in the male gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(22 reference statements)
0
1
1
Order By: Relevance
“…Male students exhibited more preference for using engagement exponents which reflected a sense of solidarity and credibility in the end of their discussions where recommendation and justification are among the major rhetorical moves (Hopkins and Dudley-Evans 1988). Surprisingly, there was a high divergence between our finding and some previous others like Tse and Hyland (2008) and Alotaibi (2021) in which engagement markers were more frequent among female writers. The former investigated book reviews and the latter examined letters of recommendation.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Male students exhibited more preference for using engagement exponents which reflected a sense of solidarity and credibility in the end of their discussions where recommendation and justification are among the major rhetorical moves (Hopkins and Dudley-Evans 1988). Surprisingly, there was a high divergence between our finding and some previous others like Tse and Hyland (2008) and Alotaibi (2021) in which engagement markers were more frequent among female writers. The former investigated book reviews and the latter examined letters of recommendation.…”
Section: Discussioncontrasting
confidence: 69%
“…The study of lexical choices associated with the use of interactional metadiscourse was the main concern of Alotaibi (2021) in a more recent study investigating gender variation in letters of recommendation. The researcher found that male and female writers differed in their choice of tokens expressing hedges and boosters.…”
Section: Previous Related Literaturementioning
confidence: 99%
“…Some research uncovers the continued prevalence of a gendered discourse that excludes certain groups (Fairchild et al, 2022). Alotaibi (2021) analyzed gender differences in letters of recommendation, revealing that male recommenders tended to utilize more hedges and boosters compared to their female counterparts.…”
Section: Research On Gender-specific Discursive Practices In the Acad...mentioning
confidence: 99%